PENGARUH LEADER MEMBER EXCHANGE (LMX) DAN MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASIONAL MELALUI KEPUASAN KERJA PADA PT. NASMOCO BAHANA MOTOR - Nabila Zalnerin Kitta (MNJ 16 UMY 125, 2016)
This research aims to analyze the influence of leader member exchange, Job Motivation, and organizational commitment trought Job Satisfaction, in PT. Nasmoco Bahana Motor. The subject in this research was employee at PT. Nasmoco Bahana Motor. In this research, sample of 133 responden were selected using population. Analysis tool used in this research is SEM ( Structural Equation Modeling) Based on the analysis that have been made the have been made the results in the influence of leader member exchange to job satisfaction and organizational commitment were negative and significant, job motivation to job satisfaction and organizational commitment were positive and significant. Keywords: Leader Member Exchange, Job Motivation, organizational commitment, Job Satisfaction.